The symbology of the sea in Lygia Bojunga Nunes's work: A reflection on utopian and dystopian framing - Eliane Aparecida Galvão Ribeiro Ferreira; Alice Atsuko Matsuda (Elos: Revista de Literatura Infantil e Xuvenil, 2014)
The ambivalent image of the sea is recurrent in Bojunga Nunes’s work. It receives a lot of symbolic meanings in her production, being sometimes a positive and sometimes a negative element. Thus, the sea is used in a utopic way, as a place for pleasure and leisure, and in a dystopic way, as scenery of a rite of passage, which includes the pain and suffering, part of the rite of passage that characterizes thebildungsromans. So, if in some texts the sea assumes a utopic character, being a place of snuggle, security, the ideal to reach, in others it is represented as dystopic, a place of distress, asphyxia and death. In this text we will study the hypothesis that, even in its dark symbolic meaning, in the author’s work the sea is an element of reflection and revelation. Thereby, it assumes metaphorically a sense of magnification of the reader’s expectative, being an element of emancipation. The objective of this text is to present a reflection on the sea’s symbolism on the mentioned texts and its importance for the reader’s formation.DOI http://dx.doi.org/10.15304/elos.1.1720